One Pot and Two Pot Synthetic Strategies and Biological Applications of Epoxy‑Chalcones - Zainab, Binti Ngaini; Saba, Farooq (The Tunisian Chemical Society and Springer Nature, 2020)
Epoxy chalcone is a heterocyclic molecule and an important precursor for the synthesis of biologically active compounds. This mini-review is elucidating the synthetic strategies of chalcone epoxide via one pot and two pot routes including nature of reactants, nature of catalyst and variety of catalyst to improve yield of desired product, biological applications and advantages and drawbacks of these synthetic strategies. One pot route has wide variety of reactants and efcient one is the condensation of aldehyde and ketone. However, two pot route is consisted of chalcone synthesis preceding to epoxy chalcone. The synthetic routes for the preparation of epoxy chalcone and the usage as a precursor for the synthesis of various organic molecules with biological application is comprehensively discussed. This review is outstanding in organic chemistry and pharmaceutical industries to produce new molecules with various applications.